Challenges of Procedures Before the ECTHR From a State Agent’s Point of View: Stocktaking of the Last 25 Years - Tallódi , Zoltán (The ECHR at 70: The Central European Narrative, 2025)
The Chapter presents the functioning of the representation of the Government before the European Court of Human Rights. It presents the establishment of the Agency of the Government in 1994. In connection with the organisation and tasks of the Agency it shows all forms of the activity of the Agency, focusing the ‘Strasbourg Proofing’, the enforcement of judgments and the promotion of human rights. The Chapter presents the whole procedure of the European Court of Human Rights, from the beginning(submitting an application) to the final phase (enforcement of judgments). The procedure of submitting an Application to the Court is a crucial point in the proceedings before the Court. The biggest challenges of the last several years are also illustrated. In connection with the prison overcrowding almost 9,000 applications had been submitted by the applicants. The domestic remedy introduced by the authorities was found effective which met the criteria set out in the pilot judgment given in the case of Varga and Others v Hungary. The problem of length of proceedings is an ongoing challenge.In 2021, a new domestic compensatory remedy was also introduced for civil court proceedings (Act no. XCIV of 2021). The judgment of 30 March 2023 in the case of Szaxon v Hungary held, that Act no. XCIV of 2021 set out an effective remedy for protracted civil proceedings. The Chapter also gives a description about the Baka Case. The role of the Parliament in the implementation of ECtHR judgments which is a lesser-known aspect of the implemtation of the judgments is also part of the Chapter. The chapter intends to demonstrate the complexity of the activities of the Agency of the Government in the European Court of Human Rights proceedings. Keywords: Agency of the Government before the European Court of Human Rights, prison overcrowding, length of proceedings, effective domestic remedy, implementation of ECtHR judgments, Strasbourg Proofing